Pengembangan Buku Ajar Pendamping Berbasis Kearifan Lokal Daerah Jombang Tema 4 Subtema 1 Kelas III - Fitria Mega Lestari; Agung Setyawan (Jurnal Pengembangan dan Evaluasi Pendidikan, 2024)
The purpose of this development research is to determine the process of developing textbooks, validity, attractiveness, and effectiveness of the Development of companion textbooks based on local wisdom in Jombang Area Theme 4 Subtheme 1. This research uses the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at UPTD SDN Baklanrayung Jombang involving 32 grade III students and UPTD SDN Tapen Jombang involving 10 grade III students. Based on the results of expert validation, the percentage of linguist validation was 82.4%, material expert validation was 95.83%, learning design expert validation was 87.5%, and teaching material design validation was 80%. The attractiveness of teaching materials was obtained from the results of the large group student response questionnaire of 94.25%. The effectiveness of teaching materials is obtained from the results of large group student learning and student activity observation sheets. Student learning outcomes obtained 95.31% which when viewed from the KKM of students class III is 100% complete. When viewed from the observation sheet of student activities, students have an interest in learning when the use of companion textbooks gets results of 81.94%. Based on the research data, it can be concluded that the companion textbook is very valid, interesting and effective to be used in theme 4 subtheme 1 class III UPTD SDN Baklanrayung Jombang.